Eight-channel spectrometric ADC with programmable logic - А. P. Voiter; M. I. Doronin; A. M. Kovalev; O. O. Gavrylov (Ядерна фізика та енергетика)
The architecture, operating principles, software and design of eight-channel spectrometric ADC with programmable logic for multiparameter measurement systems for research of nuclear reactions is considered.